GAME SEBAGAI MEDIA ALTERNATIF PENGENALAN PERMAINAN TRADISIONAL RANDAI MINANGKABAU - Purnama, Fadhli (Universitas Komputer Indonesia, 2017)
Randai is one of the traditional arts of Minangkabau. As a tradition, Randai lives with the prevailing tradition in Minangkabau society. Randai is more developed in Darek area. It is located in central West Sumatera which becomes a center of Minangkabau culture development. Randai represents a dance of people in group moving to form circle, dancing while singing, conduct sclapping and mainly serves the story. Randai has become an exclusive culture, until Randai only be played in a particular specific event. For this reason many people nowadays are not familiar with this traditional game. This alternative media is aimed to introduce Randai, how its characteristics movements and the story are played.